Factors associated with single and multiple suicide attempts in adolescents attending school in Argentina: national cross-sectional survey in 2018. Issue 4 (7th July 2022) - Pengpid, Supa; Peltzer, Karl
Abstract : Background: Factors associated with single suicide attempts (SSA) and multiple suicide attempts (MSA) may differ. Aims: The study aimed to assess the factors associated with MSA in adolescents with a history of suicide attempts during the past 12 months in Argentina. Method: National cross-sectional data from the Global School-based Student Health Survey in Argentina in 2018 were analysed. Students who reported having a history of suicide attempts in the past 12 months were included in the final sample ( n = 8507). Students with MSA were compared with students with an SSA through multiple logistic regression. Results: In a subsample of adolescents attending school (mean age 14.8 years, s.d. = 1.3), 59.4% had an SSA and 40.6% had MSA in the past 12 months. In the final adjusted logistic regression model, compared with participants with SSA, both male and female students with MSA more frequently had no close friends, reported feeling more lonely and had more anxiety-induced sleep disturbances. Furthermore, among female participants, having been physically attacked, having participated in physical fights, low parental support, current tobacco use and lifetime amphetamine use were associated with MSA. Among male students, multiple sexual partners were associated with MSA. Furthermore, among both boys and girls, compared with participants without psychosocial distress, participants with one, two, three or more psychosocial distress factors had higher odds of MSA. Compared with students with one or two social or environmental risk factors, students with seven or eight social or environmental risk factors had higher odds of MSA; compared with students who had zero or one health risk behaviours, students with six or more health risk behaviours had higher odds of MSA. Conclusions: Psychosocial distress (anxiety-induced sleep disturbance, having no close friends and loneliness) increased the odds of MSA among both sexes. The odds of MSA were increased by interpersonal violence, low parental support and substance use among girls, and by having multiple sexual partners among boys. This suggests the potential relevance of these variables in identifying multiple suicide attempters among adolescents attending school in Argentina.